Perilaku Konsumen Masyarakat Pedesaan Kecamatan Merawang Provinsi Kepulauan Bangka Belitung di Era Revolusi Industri 4.0 - Tria, Fuji; Melia, Hilda (Universitas Muhammadiyah Pontianak, 2019)
Rural areas are often linked to the lagging development of ways of life compared to modern life in urban areas. Consumers are an important element in consumer behavior, so an effort to market a product, a sales manager must analyze, study, and understand the behavior of prospective consumer consumers, it will take the consumer's point of view obtained to can reevaluate and respond to needs quickly. Therefore, consumer needs that underlie consumer behavior must be fully understood plus rural consumers who are often considered to be underdeveloped consumers how to transact in the industrial revolution 4.0 era. The purpose of this study is to know and analyze the influence of consumer behavior factors consisting of personal , social, and technology simultaneously towards decisions on digital-based products in 4.0 era in the village of Pagarawan and Balunijuk. The analysis technique uses multiple regression analysis. The simulataneous test results show that personal, social, and technological factors have a significant effect on the decision of digital-based products in 4.0 era in the village of Pagarawan and Balunijuk. While the results of partial testing show that all variables chosen as research models each have a positive and significant influence on the decisions of digital-based products in 4.0 era in Pagarawan and Balunijuk villages, Merawang sub-district.